Mathematics simulations - Pelangi Multimedia Technologies Sdn. Bhd.; Penerbitan Pelangi Sdn. Bhd. (Selangor : Pelangi Multimedia Technologies Sdn. Bhd. : Penerbitan Pelangi Sdn. Bhd. (distributor), 2006)
This cd-rom provides questions that can be generated infinitely by computers, parameters of simulations can be set and its results can be shown in real time. All simulations are calculated based on mathematics formula to ensure that the result are accurate
PTSL : volume 1 ; volume 2
System requirements : Windows 98/Me/2000/XP
Keywords: Mathematics -- Study and teaching -- Simulation methods; Mathematics -- Study and teaching (Secondary); Mathematics